Synthesis of Silver Nanoparticles Mediated by Fungi: A Review - Guilger-Casagrande, Mariana; Lima, Renata de (Frontiers in Bioengineering and Biotechnology, 2019)
The use of fungi as reducing and stabilizing agents in the biogenic synthesis of silver nanoparticles is attractive due to the production of large quantities of proteins, high yields, easy handling, and low toxicity of the residues. Furthermore, this synthesis process coats the nanoparticles with biomolecules derived from the fungus, which can improve stability and may confer biological activity. The aim of this review is to describe studies in which silver nanoparticles were synthesized using fungi as reducing agents, discussing the mechanisms and optimization of the synthesis, as well as the applications. The literature shows that various species of fungus have potential for use in biogenic synthesis, enabling the production of nanoparticles with different characteristics, considering aspects such as their size, surface charge, and morphology. The synthesis mechanisms have not yet been fully elucidated, although it is believed that fungal biomolecules are mainly responsible for the process. The synthesis can be optimized by adjusting parameters such as temperature, pH, silver precursor concentration, biomass amount, and fungus cultivation time. Silver nanoparticles synthesized using fungi enable the control of pathogens, with low toxicity and good biocompatibility. These findings open perspectives for future investigations concerning the use of these nanoparticles as antimicrobials in the areas of health and agriculture.